2018
DOI: 10.1186/s13046-018-0742-2
|View full text |Cite
|
Sign up to set email alerts
|

Mature and progenitor endothelial cells perform angiogenesis also under protease inhibition: the amoeboid angiogenesis

Abstract: BackgroundControlling vascular growth is a challenging aim for the inhibition of tumor growth and metastasis. The amoeboid and mesenchymal types of invasiveness are two modes of migration interchangeable in cancer cells: the Rac-dependent mesenchymal migration requires the activity of proteases; the Rho-ROCK-dependent amoeboid motility is protease-independent and has never been described in endothelial cells.MethodsA cocktail of physiologic inhibitors (Ph-C) of serine-proteases, metallo-proteases and cysteine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Through its interaction with integrins, we previously reported that uPAR is able to affect melanoma invasion, migration and response to therapy 33 . We also demonstrated that the M25 linear peptide was able to uncouple uPAR from integrins thus affecting its functions 33,34 . On the basis of these evidences, we reasoned that inhibition of uPAR functions with M25 peptide could produce functional effects similar to those obtained with uPAR silencing by means of si-uPAR.…”
Section: Mir-378a-5p Negatively Regulates Hoxd10 Expressionmentioning
confidence: 77%
See 1 more Smart Citation
“…Through its interaction with integrins, we previously reported that uPAR is able to affect melanoma invasion, migration and response to therapy 33 . We also demonstrated that the M25 linear peptide was able to uncouple uPAR from integrins thus affecting its functions 33,34 . On the basis of these evidences, we reasoned that inhibition of uPAR functions with M25 peptide could produce functional effects similar to those obtained with uPAR silencing by means of si-uPAR.…”
Section: Mir-378a-5p Negatively Regulates Hoxd10 Expressionmentioning
confidence: 77%
“…Inhibition of uPAR-integrin interaction was obtained with the M25 peptide (STYHHLSLGYMYTLN), previously identified in a phage display library 55 and produced by PRIMM srl (Milan, Italy). Its sequence spans an exposed loop on the ligand-binding surface of integrin α chain and uncouples the interaction of the α-chain of integrin with uPAR, thus impairing uPAR functions 33,34 .…”
Section: Treatment Of Cells With M25 Peptidementioning
confidence: 99%
“…In this paper we provide a strong evidence that the well known and characterized uPA receptor (uPAR) acts not only as a promoter of proliferation, invasiveness and angiogenesis in melanoma and other cancer cell lines [[42], [43], [44], [45]] but also as a factor contributing to the development of drug resistance. Indeed, we found a remarkable direct association between uPAR and EGFR co-expression levels and vemurafenib responsiveness inV600E BRAF mutated melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, uPAR is a glycosylphosphatidylinositol-anchored membrane protein which associates with integrins and RTKs such as EGFR to form a potent signaling complex [31,37,45]. uPAR is overexpressed in many human malignancies including melanomas [[46], [47], [48], [49]] and is associated with a worse prognosis especially among breast cancer and esophageal carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Our results reveal that SND1 facilitates the proliferation and invasion of glioma cells. We identified RhoA, a small GTPase implicating cancer proliferation, apoptosis, angiogenesis, migration, and invasion, [11][12][13][14] as a potential target of SND1 through human GBM mRNA profiling and bioinformatics analyses. The regulatory mechanism and biologic effects of SND1 and RhoA were also determined.…”
Section: Neuro-oncologymentioning
confidence: 99%